PERSEPSI MAHASISWA TERHADAP PEMBERITAAN JURNALISME SASTRAWI DI MAJALAH TEMPO (Jurnal Washiyah: Jurnal Kajian Dakwah dah Komunikasi, 2020)
Writing news with the literary journalism techniques has advantages in terms of conveying the facts to its reader. Literary journalism makes it  almost impossible to hide the facts in the news. Because the news is no longer delivered by chronological form, but in the form of reporting facts which has been dramatized in such a way. Journalists observe their object like a novel writers who seek and obtain reality from narration. On the other hand, reporting of literary journalism also meant in human interest. Seeing an event with a different glasses to touch the human side of the news source. This was intend so that readers can feel and be a part of the event. The purpose of this study was to determine the perceptions of student activists as a campus journalists on the credibility of the literary journalism news in the July 15-21 edition of Tempo. To find out the perception of student activists as campus journalists on the literary technique of literary journalism news in Tempo, July 15-21, 2019 edition.